Tropical storms and mortality under climate change. (May 2019) - Pugatch, Todd
Highlights: I quantify the effect of tropical storms on mortality in Mexico using meteorological data. I estimate that storms killed 1598 people in Mexico from 1990 to 2011. I project that storm deaths would increase by as much as 52% under climate change. These projections hold population and income at contemporaneous levels. Abstract: Extreme weather induced by climate change can have major consequences for human health. In this study, I quantify the effect of tropical storm frequency and severity on mortality using objective meteorological data and the universe of vital statistics records from a large developing country, Mexico. Using a measure of storm exposure that accounts for both windspeed dispersion and population density along the storm track, I project changes in past storm-related mortality under various scenarios of continued climate change, while holding population and income at contemporaneous levels. I find that storm-related deaths would have risen under most climate change scenarios considered, with increases of as much as 52% or declines of as much as 10%, depending on the interplay between increasing storm severity and decreased frequency.